Identifying Discrepancies in Gestational Diabetes Mellitus Postpartum Follow-Up During Care Transitions - Brittany Strelow DMSc, MS, PA-C; Justine Herndon PA-C, MS; Alex Ferrier BS; Madysen McCormick BS; AnneMarie McMahon BS; Emily Schlechtinger BS; Deborah Shefa BS; Mark Takagi MEng; Rozalina McCoy MD, MS; Rachel Olson MSc, PhD; Danielle O'Laughlin PA-C, MS (SAGE Publishing, 2023)
Background: Gestational diabetes mellitus (GDM) is a common complication of pregnancy that carries lasting risks. For women who have a history of GDM, the risk of developing type 2 diabetes mellitus (T2DM) increases by 50 to 60%. To monitor and prevent the development of T2DM, guidelines suggest screening those with a history of GDM at 6-weeks and 3-years post-delivery. For patients with abnormal lab results at the 6-week mark, it is advised to complete lab work sooner, at the 1-year mark. Data suggests that these guidelines are not being followed globally, and most do not receive adequate screening for T2DM. Methods: A retroactive chart review of 203 women between 18 and 55 years old with a past medical history significant for GDM was conducted to determine if patients with GDM completed screening for T2DM at 6-week, 1-year, and 3-year timestamps post-delivery. Patient demographics (age, race, ethnicity, language), clinical characteristics (body mass index), provider gender, and whether prediabetes or T2DM developed were recorded. Patients who did not complete the required follow-up received educational materials via the online portal system, and hemoglobin A1c (HbA1c) screening tests were ordered. Results: Ninety days post-intervention, 38 patients (50%) completed the HbA1c screening test, which exceeded our goal of a 5% improvement. Age and BMI 1-year postpartum were found to be significant factors in whether a patient completed HbA1c screening, with 16/18 (89%) completing screening with a healthy BMI 1-year postpartum (18.5 ≤ BMI < 25.0) but only 11/41 (27%) completing screening for patients under 40 years with an unhealthy BMI 1-year postpartum. Of the 38 patients who completed HbA1c screening, 9 (23.7%) had abnormal screening results. Conclusion: Follow-up surveillance for T2DM among women with a history of GDM is poor. Electronic health records can be used to identify and rectify gaps in care. Dissemination of standardized educational materials and electronic order entry for patients improved screening between the handoff from obstetrics to primary care.